KARAKTERISTIK DAN KLASIFIKASI TANAH RAWA PASANG SURUT DI KARANG AGUNG ULU SUMATERA SELATAN - YULIANA, E. DEWI (Buletin Udayana Mengabdi; Vol 8 No 1 (2009): Volume 8 No.1 – April 2009, 2012)
ABSTRACT This study is aimed at identifyimg the characteristics and classification of soil in South Sumatera Swamp area. This experiment was performed in pasang surut area located in swamp development project. Using soil description method and followed by soil analysis in soil chemistry lab of IPB, it was found that the soil is classified as Typic Sulfaquent, sangat halus, isohipertermik.